Perancangan Sistem Informasi Stock Opname untuk Mengurangi Selisih Aset pada PT XYZ - Nursyanti, Yevita; Zahra, Azkiya (Jurnal Teknik dan Teknologi Tepat Guna, 2026)
The discrepancy in productive asset units at PT XYZhas become a serious issue, resulting in a financial loss of Rp 947.423.313 in 2024 and causing a delay in the stock opname recap process of more than one month, exceeding the company's Key Performance Indicator (KPI) deadline. This study aims to design an information system for stock opname that reduces asset data discrepancies, improves recap efficiency, and enhances the accuracy of asset recording. The research method involves the use of a fishbone diagram and 5W+1H analysis to identify the root causes of the problem. The analysis reveals that the main contributing factor is the manual method using physical forms (Count Tags), which are prone to loss and data entry errors. Therefore, a digital-based information system design is proposed using Use Case Diagram, Activity Diagram, and Context Diagram modeling. This system is expected to reduce asset discrepancies, improve recap efficiency, and enhance data recording accuracy for productive assets at PT XYZ